Comparative Efficacy Evaluation of Regular and Probiotic Yoghurts for the Treatment of Acute Watery Diarrhoea in Children at a Tertiary Care Hospital - Vivek Parikh; Ghanshyam G. Patel (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Acute diarrhea (AD) represents the most prevalent gastroenterological condition and is a leading cause of dehydration among children. This condition predominantly affects children under the age of five. Hence; the present study was conducted for comparative efficacy evaluation of regular and probiotic yoghurts for the treatment of acute watery diarrhoea in children at a tertiary care hospital. Materials & Methods: A total of 40 pediatric subjects were enrolled. Only those subjects were enrolled which had history of acute watery diarrhea from the past three days. All the subjects were randomized into two study groups as follows: Regular yogurt group (n=20) and probiotic yogurt group (n=20). The participants were provided with a nutritional diet alongside a low osmolality oral rehydration solution (ORS). Furthermore, those in the regular yogurt group were administered 15 mg/kg of regular yogurt every four to six hours for a duration of five days. Similarly, participants in the probiotic yogurt group received 15 mg/kg of commercially available probiotic yogurt at the same intervals over the five-day period, in addition to the nutritional diet and low osmolality ORS. Outcome was evaluated. All the results were summarized in Microsoft excel sheet and were subjected to statistical analysis using SPSS software. Results: Mean age of the subjects of regular yogurt group and probiotic yogurt group was 10.8 years and 9.7 years respectively. Majority proportion of subjects were boys among these two study groups. Among regular yogurt groups, frequency of acute diarrhea on the first day, second day, third day, fourth day and fifth day were 8.2, 7.5, 4.9, 2.9 and 1.8 respectively. Among regular yogurt groups, frequency of acute diarrhea on the first day, second day, third day, fourth day and fifth day were 7.8, 7.1, 5.3, 2.5 and 2.1 respectively. Significant improvement was seen in both the study groups. However, while making inter-group comparisons at different time intervals, non-significant results were obtained. Conclusion: The findings of our study indicate that both probiotic and conventional yogurts exert beneficial effects on the management of acute diarrhea in children. Our results suggest that conventional yogurt may offer similar therapeutic benefits as probiotic yogurt in the treatment of diarrhea.